2021
DOI: 10.1590/1414-431x202010084
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chronic obstructive pulmonary disease on linear and nonlinear dynamics of heart rate variability in patients with heart failure

Abstract: The objective of this study was to investigate the impact of chronic obstructive pulmonary disease (COPD)-heart failure (HF) coexistence on linear and nonlinear dynamics of heart rate variability (HRV). Forty-one patients (14 with COPD-HF and 27 HF) were enrolled and underwent pulmonary function and echocardiography evaluation to confirm the clinical diagnosis. Heart rate (HR) and R-R intervals (iRR) were collected during active postural maneuver (APM) [supine (10 min) to orthostasis (10 min)], respiratory sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(37 reference statements)
0
6
0
2
Order By: Relevance
“…RR → HR can also serve as a prognostic digital marker of recovery from cardiorespiratory complication(s) through exercise. This suggestion becomes plausible, given the association between decreased respiratory modulation of the cardiac function and the cardiorespiratory pathology [129, 130]. Considering the benefit of exercise-therapy to COVID-19 recovery [131], RR → HR can help monitor the patients’ progress and their recovery by quantifying the degree of increase in their respiratory modulation of their cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…RR → HR can also serve as a prognostic digital marker of recovery from cardiorespiratory complication(s) through exercise. This suggestion becomes plausible, given the association between decreased respiratory modulation of the cardiac function and the cardiorespiratory pathology [129, 130]. Considering the benefit of exercise-therapy to COVID-19 recovery [131], RR → HR can help monitor the patients’ progress and their recovery by quantifying the degree of increase in their respiratory modulation of their cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…31 Finally, a recent study also revealed that COPD patients with heart failure had no response in HRV indices during postural changes (with controlled breathing) and exhibited higher high-frequency (vagal) components compared with heart failure patients without respiratory problems. 6 In healthy individuals, acute exposure to hypoxia leads to decreased cardiac ANS modulation, both at rest 32 and in response to exercise. This is due to either a reduction of vagal stimulation or by an SNS predominance or a combination of both responses.…”
Section: Discussionmentioning
confidence: 99%
“…4 In patients with chronic obstructive pulmonary disease (COPD), although diurnal variation in heart rate variability (HRV) was normal, impairments in HRV during a stimulus have been reported. 5,6 Long-term oxygen therapy seems to improve the HRV dysfunctions. 7,8 Similar observations have been also reported in patients with pulmonary arterial hypertension (PAH); they exhibit blunted baroreflex sensitivity which was related to reduced exercise capacity and has been proposed as an additional marker of disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that reduced oxygen supply (O 2 ), systemic inflammation and increased oxidative stress can contribute to respiratory muscle dysfunction (9,(12)(13)(14). In this context, an understanding of the interaction between the mechanisms that lead to symptoms during exercise such as dyspnea, can provide useful information about both diseases (15).…”
Section: Impact Of Copd-chf On Exercise Capacity and Symptomsmentioning
confidence: 99%
“…In this context, there are several lines of evidence suggesting that oxygen delivery to working muscles may be critically impaired during dynamic exercise in COPD-CHF patients ( 9 ). In addition, another impact in patients with COPD-CHF are ventilatory inefficiency and peripheral muscle dysfunction characterized by reduced muscle strength, promoting negative consequences on exercise performance ( 9 , 13 ).…”
Section: Impact Of Copd-chf On Exercise Capacity and Symptomsmentioning
confidence: 99%